Brchli1 mutation induces bright yellow leaves by disrupting magnesium chelatase I subunit function in Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Liu, Chuanhong; Chai, Yi; Tan, Chong; Shi, Fengyan; Zhang, Yun; Liu, Zhiyong (Frontiers in Plant Science, 2024)
Magnesium chelatase (MgCh) plays a pivotal role in photosynthesis, catalyzing the insertion of magnesium into protoporphyrin IX (Proto IX), a key intermediate in chlorophyll (Chl) biosynthesis. MgCh is a heteromeric complex composed of the MgCh D subunit (CHLD), the MgCh H subunit (CHLH), and the MgCh I subunit (CHLI). The bright yellow leaves (byl) mutant was obtained through ethyl methanesulfonate (EMS) mutagenesis of the 'FT' Chinese cabbage (Brassica rapa L. ssp. pekinensis) doubled haploid line, whose Chl content, net photosynthetic rate (Pn), and non-photochemical quenching coefficient (NPQ) were decreased, and whose chloroplast development was incomplete. byl recovered to a light green phenotype under weak light conditions. Genetic analysis revealed that the bright yellow leaves phenotype of byl was caused by a single recessive nuclear gene. Using Mutmap sequencing and Kompetitive allele-specific PCR (KASP) identification, BraA01g010040.3.5C, encoding the CHLI subunit of MgCh, was identified as the candidate gene and named Brchli1. A nonsynonymous G-to-A mutation in the Brchli1 exon resulted in the substitution of aspartic acid with asparagine. Brchli1-silenced Chinese cabbage displayed bright yellow leaves with decreased Brchli1 expression. Transiently overexpressed Brchli1 in the byl mutant restored the green leaf phenotype and significantly increased relative Brchli1 expression levels. Both BrCHLI1 and its mutated variant were localized in chloroplasts. Yeast two-hybrid and luciferase complementation imaging assays demonstrated that BrCHLI1 interacted with both BrCHLD and itself. BrCHLI1 mutations did not affect its interaction with BrCHLD. 3 Together, Brchli1 mutations impaired the function of MgCh, providing insights into the molecular mechanism of leaf coloration.